The experience of receiving mental health care for people with personality disorder - Speldewinde, Donald Cecil (Curtin University, 2016)
This thesis uses mixed methods research to document the experiences of people diagnosed with a personality disorder when they access health care during times of crisis. Eighty-one people participated in the quantitative component and eleven in the qualitative section of the research. While participants spoke of improvements in the attitudes of health professionals their care remained ad hoc and was generally dependent on the attitudes of individual health professionals when they presented for care.